Re-evaluation of the taxonomy of Gelidocalamus stellatus (Poaceae: Bambusoideae) and its infraspecific taxa from southern China - Nie, Tang-Jie; Li, Wei-Jian; Ji, Xue-Nan; Liu, Yu-Guang; Li, Zu-Yao; Yang, Guang-Yao; Zhang, Wen-Gen (Phytotaxa, 2018)
In the present study, a classical taxonomic analysis of micromorphological characters of the leaf epidermis was employed to reassess the taxonomy of Gelidocalamus stellatus and its infraspecific taxa from southern China. We propose that G. monophyllus is distinct from G. stellatus, and G. wugongshanensis should be treated as a variety under G. stellatus. The variety, i.e. G. stellatus var. mangshanensis, collected from the Mangshan of Hunan Province in China, is re-described and illustrated. A formal taxonomic treatment is presented, including descriptions, comments, illustrations, distribution maps, and SEM images of the abaxial leaf epidermis.